Improving Relay Running Learning Outcomes Through Modifying Learning Media for Class V Students at SD N 2 Menggamat - Kamaluddin (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2023)
The general objective of this research is to enhance student outcomes through the implementation of Relay Race Learning using modified instructional media. Additionally, this study aims to obtain in-depth information about the application of instructional media in relay race material. The research design employed is Classroom Action Research (CAR). The subjects in this study are 12 students from class V at SD N 2 Menggamat. The research was conducted over two meetings spanning two cycles. Each cycle consisted of four stages. The first cycle indicated that through action, students can self-motivate. From this first cycle, the result was 17%, indicating it was incomplete. The second cycle, as a reflection of the first cycle, also demonstrated that action improves student learning outcomes. The result of the second cycle was 75%, indicating completion. Based on the findings of this research, it can be concluded that: (1) Relay race learning using modified instructional media enhances student learning outcomes, (2) Relay race learning using modified instructional media motivates students and encourages active participation in the learning process.